A strategic goal analysis of options for tuna longline joint ventures in Southeast Asia Indonesia-Japan case study. - Marten, Gerald; Matsuda, Yoshiaki; Bardach, John.; Comitini, Salvatore; Hardjolukito, Sutanto (Honolulu, Hawaii East-West Center, 1981)
Research report/East-West Environment and Policy Institute; no. 3
Keywords: Joint ventures--Indonesia.; Joint ventures--Japan.; Fishery policy--Indonesia; Japan; Long lining (Fisheries)--Indonesia; Japan; Tuna fisheries--Indonesia; Japan